Live and dead deep-sea benthic foraminiferal macrofauna of the Levantine basin (SE Mediterranean) and their ecological characteristics. (June 2018) - Hyams-Kaphzan, Orit; Lubinevsky, Hadas; Crouvi, Onn; Harlavan, Yehudit; Herut, Barak; Kanari, Mor; Tom, Moshe; Almogi-Labin, Ahuva
Abstract: The present study sought to quantitatively characterize the live and dead benthic foraminifera communities of the deep southeastern Levantine basin of the Mediterranean Sea (33.4º–31.7 ºN, 31.3º–34.9 ºE; 100–1900 m water depth) and their relationships to environmental conditions. Box corer samples were collected at 50 sites between June and July 2013. The foraminiferal macrofauna (> 250 µm) were enumerated and identified (76% to the species level). Six live foraminiferal assemblages were identified, inhabiting six biotopes, the shelf margin (SM), two upper continental slopes (UCS1 and UCS2), the lower continental slope (LCS), the eastern bathyal plain (EBP) and the western bathyal plain (WBP). The dead communities were divided into four biotopes, generally compatible with the live ones, excluding the UCS2 and the EBP. The foraminiferal density in the various live biotopes was relatively stable across the studied area, excluding the UCS2 and EBP, unlike the density of the dead shells, which increased with depth. The number of taxa per biotope was estimated by rarefaction curves and compared to the observed numbers, with a decreasing number of live taxa with water depth. The alpha-diversity, which was evaluated in relation to the number of sampled individuals, reached an asymptote in all biotopes, with very low values in the WBP. The within-biotope heterogeneity was evaluated by the average Chao-Sørensen similarity index and by a beta-diversity index (exp(gamma diversity) - exp(alpha diversity)), revealing variable heterogeneities in both assemblages. Water depth, sediment grain size mode, CaCO3 (wt%), and clay fraction (wt%) were jointly but feebly correlated with live faunal composition. Highlights: Live and dead deep sea (100-1900m) macro-foraminifera (>250μm) were studied for the first time in the SE Mediterranean Sea. 100 live and 197 dead benthic foraminiferal species were identified based on sampling of 50 sites. Shelf margin, upper slope, lower slope and bathyal plain biotopes were identified based on the living and dead assemblages. Foraminiferal density was fairly stable in the live biotopes, unlike the density of the dead shells, increasing with depth. Species diversity of live taxa per biotope decreased with depth, being the highest in the upper slope.